2001
DOI: 10.1084/jem.194.6.781
|View full text |Cite
|
Sign up to set email alerts
|

C1q and Mannose Binding Lectin Engagement of Cell Surface Calreticulin and Cd91 Initiates Macropinocytosis and Uptake of Apoptotic Cells

Abstract: Removal of apoptotic cells is essential for maintenance of tissue homeostasis, organogenesis, remodeling, development, and maintenance of the immune system, protection against neoplasia, and resolution of inflammation. The mechanisms of this removal involve recognition of the apoptotic cell surface and initiation of phagocytic uptake into a variety of cell types. Here we provide evidence that C1q and mannose binding lectin (MBL), a member of the collectin family of proteins, bind to apoptotic cells and stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
931
8
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,037 publications
(979 citation statements)
references
References 124 publications
23
931
8
7
Order By: Relevance
“…However, this leaves us with the obvious question, what kind of effector machinery does MBL utilize to remove apoptotic cells? Two recent studies have brought further insight to this question indicating that both C1q, SP-A, SP-D as well as MBL utilize the calreticulin/CD91 complex on phagocytes as acceptor site for sequestration of apoptotic material [9,16]. Consistent with these studies, we demonstrated that opsonization of apoptotic cells with MBL facilitated their uptake by macrophages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, this leaves us with the obvious question, what kind of effector machinery does MBL utilize to remove apoptotic cells? Two recent studies have brought further insight to this question indicating that both C1q, SP-A, SP-D as well as MBL utilize the calreticulin/CD91 complex on phagocytes as acceptor site for sequestration of apoptotic material [9,16]. Consistent with these studies, we demonstrated that opsonization of apoptotic cells with MBL facilitated their uptake by macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the presence of MBL variant alleles is associated with increased risk of SLE (for a comprehensive analysis see [8]). Recent findings show that MBL binds to apoptotic cells and that both C1q and MBL use calreticulin and CD91 to initiate macropinocytosis and uptake of apoptotic cells by phagocytes [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that such 26 TROELSEN ET AL endothelial cell damage would lead to the endothelial dysfunction that has been described in RA (39,40), which again is predictive of the development of coronary artery disease (41). It is of particular interest that MBL, among other factors, binds N-acetylglucosamine and damaged host cells, exposing nucleic acids (42)(43)(44). Oxidative stress seems to expose structures on endothelial cells that promote binding of MBL (14).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in the recognition and uptake of apoptotic cells have been thought to contribute to the pathogenesis of autoimmunity in SLE (8,25). A disturbed clearance of apoptotic cells, as has been observed in some patients with SLE, facilitates the release of heat-shock proteins (33), nucleosomes (34), calreticulin (35,36), and other intracellular contents. In addition, modifications of these autoantigens during programmed cell death can render them more immunogenic (34,37,38).…”
Section: Discussionmentioning
confidence: 99%